Identificação de polipeptídeos e proteínas antimicrobianas da hemolinfa da broca-da-cana diatraea saccharalis (lepidoptera: crambidae) por análise proteômica - Rocha, Iara Fernanda (2015)
Diatraea saccharalis is an important insect pest of sugarcane and other crops, so it has been the focus of research. In general, the insects present innate immune system, which come with a range of immune responses against microorganisms. Many antimicrobial peptides have been isolated and characterized from model insects such as Drosophila melanogaster and Bombyx mori. In the 5th instar larvae of Diatraea saccharalis has already been reported a protein of Gloverin family with antimicrobial activity. Considering these facts, the objectives of this study were to determine the protein profile of hemolymph larvae from Diatraea sacharalis at 5th instar challenged with Escherichia coli (ATCC 11224) and Bacillus subtilis (ATCC 6623), identify differentially expressed proteins and polypeptides by analyzing the proteomic data, and verifying the antimicrobial activity of crude extract on plates by inhibition of microbial growth. Proteins from the hemolymph of larvae of D. sacharalis challenged and unchallenged were extracted. The samples were quantified and subjected to two-dimensional electrophoresis (2-DE) to obtain a proteomic profile of native hemolymph, challenged by E. coli and B. subtilis. Each gel showed an average of 300 protein spots and 92 spots were correspondents in these gels on three conditions. Were taken 41 different protein spots from gels, these spots were digested with trypsin and analyzed by mass spectrometry of the type MALDI-TOF/TOF. In this analysis, it was possible to identify 10 proteins from MS and MS/MS spectra. Among these proteins were expressed by induction with both bacteria such as chitinase and antimicrobial peptides: protein homologous to the turandot (turandot the like-protein), protein homologous to attacin (Attacin like-protein), and protein homologous peptidoglycan recognition. Another antimicrobial peptide was found, the homologous to β-defensin (β-defensin-like protein), induced only in the hemolymph of the larvae challenged by B. subtilis. A homologous protein Cyclophilin (Cyclophilin-like protein) was found in the hemolymph of larvae challenged and non-challenged. In addition, were also found proteins with hatching activity, hydrolytic not characterized and hypothetical protein of unknown function. Additionally, it also tested the antimicrobial activity of crude extracts from the hemolymph, by testing inhibition of microbial growth plate area, and this analysis was observed inhibition of growth of B. subtilis with the hemolymph extract from larvae challenged with B. subtilis. This is the first analysis of proteomic profile of hemolymph of a major agricultural pest, which verified the expression of some proteins with several functions and four related proteins immune response. These results contribute to the understanding of the immune system D. saccharalis under condition of infection.